Systemic Complications Resulting from Odontogenic Infection: A Case Report - Gabriella Miyashiro Facundes; Maria Fernanda de Oliveira; Pâmela Luenny Forte Santos; Tamara Brito da Silva; Aristéa Ribeiro Carvalho; Kalil de Sousa Castro; Eliane Ferreira Sampaio; Alinne Patierry Oliveira Pacífico Feitosa (Archives of Current Research International, 2025)
Intensive Care Units (ICUs) aim to meet the care needs of patients requiring continuous observation by an interdisciplinary and multidisciplinary team, with the dentist playing a key role in adapting to the patient’s needs, prioritizing their healing process and well-being according to their condition. This is particularly relevant in cases of periapical infection, the most common form of odontogenic infection, which, though often localized, can spread and lead to serious complications such as Mediastinitis, an inflammation of the mediastinum in the loose connective tissue.This report aims to present the hospital management of the treatment of a dental-origin infection, starting in the lower left third molar, which affected the mediastinum, thus highlighting the importance of having a dentist in ICUs. It was conducted at the Dr. Carlos Alberto Studart Gomes Hospital in Messejana (HM), where a female patient, without comorbidities, was admitted with a history of a dental abscess affecting the oral space, along with fever, tachycardia, intense dyspnea, edema, and other symptoms. She presented persistent toxemia (marked leukocytosis of 22,400 mm³ and elevated CRP of 22.90), thrombocytosis, and a marked edematous syndrome in the lower limbs. A combined surgery between Dentistry and Cardiac Surgery was indicated, which performed a pericardiostomy. The dental team extracted the tooth involved, performed an extraoral puncture of the affected facial space, submandibular drainage, and installed a drain. Fifteen days post-operatively, the patient showed good healing, with no signs or symptoms of inflammation or persistent infection. Laboratory tests also showed significant improvement (leukocytes 12,000 mm³ and CRP 9 mg/L), and she was discharged from the hospital.